Implementasi Kebijakan Program Keluarga Harapan (PKH) di Bidang Pendidikan (Studi Kasus di Kelurahan Kota Matsum IV Kecamatan Medan Area) - Nurul Jannah; Indra Muda; Bahrum Jamil (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2022)
Education is the process of influencing learnes to adapt to the environment and can bring about changes in borth within and within the community. However, the scarcity of economics precludes schooling and even dropouts because they help families make ends meet. The study aims to know the implementation of policies and obstacles in the hope family program in Matsum IV district Medan Area. The study employs qualitative methods in which it is descriptive that give a clear picture of the problem at hand. Data collection techniques through interviews to informants who know information about the implementation of PKH policy, literature studies, observation, and documentation to support the results of the interview. The study shows tha the implementation of executive policy PKH in Matsum IV, Medan Area has been seen from the few factors which are   standard   and   target   policy,  human   reseources   and   money   reseources,   executive   agent   PKH characteristics assist the recipient well, executive organization communication is well established, the social, economic, and political environment supports PKH. The study is based on the fact that the economic growth in the country will be affected mainly by education, with the existence of so- called debtors, it is possible to send their children to school even if there is a problem.